Combination of scaffold with adipose-derived mesenchymal stem cell on knee joint cartilage defects: A literature review - Japamadisaw, Aliefio; Hernugrahanto, Kukuh Dwiputra; Utomo, Dwikora Novembri (Edelweiss Applied Science and Technology, 2024)
Knee joint cartilage defects are a significant clinical challenge due to the limited regenerative capacity of articular cartilage, often leading to joint degeneration and osteoarthritis (OA). Conventional treatment methods, such as surgical repair and conservative management, frequently fail to restore cartilage function fully. In recent years, scaffold-based tissue engineering using adipose-derived mesenchymal stem cells (ADMSCs) has emerged as a promising strategy for cartilage regeneration. ADMSCs, known for their abundant availability, ease of isolation, and chondrogenic potential, provide a viable cellular source for repairing damaged cartilage. When combined with biocompatible scaffolds, ADMSCs can enhance tissue regeneration by promoting cell proliferation, differentiation, and extracellular matrix (ECM) formation at the injury site. Various scaffold materials, including natural and synthetic polymers, have been explored to provide the structural support necessary for cell attachment and tissue formation. This literature review examines the current advancements in the application of ADMSC-loaded scaffolds for knee joint cartilage defects, focusing on their biological properties, scaffold designs, and the outcomes of preclinical and clinical studies. The review also addresses the challenges, such as scaffold degradation, mechanical properties, and cellular migration, that must be optimized for successful clinical translation. Overall, this review highlights the potential of ADMSC-based scaffold systems to offer a viable solution for knee cartilage repair and provides insights into future directions for improving therapeutic strategies in cartilage tissue engineering.